The effect of porcelain thickness and surface liner application on the fracture behavior of a ceramic system - Benetti, Paula [UNESP]; Pelogia, Fernanda [UNESP]; Valandro, Luiz Felipe; Bottino, Marco Antonio [UNESP]; Della Bona, Alvaro (Elsevier B.V., 2011)
Objectives. To determine the effect of porcelain thickness and the application of a surface liner (SL) on the flexural strength (sigma) of a ceramic system.Methods. One hundred twenty bar-shaped specimens of yttria-stabilized zirconia-based ceramic were fabricated and randomly divided into two groups according to the application of SL: A-applied; B-not applied. The specimens were further divided according to the porcelain veneer thickness (n = 20): 0-0.5 mm; 1-1.0 mm; 2-2.0 mm. All specimens were tested in 3-point bending with the porcelain under tension. The maximum load was recorded at first sign of fracture, the sigma was calculated and the mode of failure was determined. Data was statistically analyzed using one-way ANOVA, Tukey (alpha = 0.05) and Weibull distribution.Results. The SL application had no effect (p = 0.723) while the porcelain thickness had a significant effect (p = 0.000) on the mean sigma values. No significant differences in mean sigma values were found with same porcelain thickness. A 0.5-mm thick porcelain layer (groups A0 and B0) showed greater mean sigma values than other groups. The Weibull modulus (m) ranged from 6 (groups A1 and B2) to 9 (groups A0, A2 and B0). The predominant mode of failure for all groups was fracture initiation at the porcelain surface propagating to the ceramic interface.Significance. The porcelain thickness influenced the mean sigma values, but the SL had no significant effect on the flexural strength and the mode of failure of the ceramic system examined. (C) 2011 Academy of Dental Materials. Published by Elsevier Ltd. All rights reserved.
Keywords: Ceramic; Flexural strength; Thickness; Liner; Stress concentration